Designed Single-Step Synthesis, Structure, and Derivative Textural Properties of Well-Ordered Layered Penta-Coordinate Silicon Alcoholate Complexes - Li, Xiansen (2014)
The controllable synthesis of well-ordered layered materials with specific nanoarchitecture poses a grand challenge in materials chemistry. We report the solvothermal synthesis of two structurally analogous 5-coordinate organosilicate complexes via a novel transesterification mechanism. Since the polycrystalline nature of the intrinsic hypervalent Si complex thwarts the endeavor in determining its structure, a novel strategy concerning the elegant addition of a small fraction of B species as an effective crystal growth mediator and a sacrificial agent is proposed to directly prepare diffraction-quality single crystals without disrupting the intrinsic elemental type. In the determined crystal structure, two monomeric primary building units (PBUs) self-assemble into a dimeric asymmetric secondary BU via strong Na(+)-O(2−) ionic bonds. The designed one-pot synthesis is straightforward, robust, and efficient, leading to a well-ordered (10ī)-parallel layered Si complex with its principal interlayers intercalated with extensive van der Waals gaps in spite of the presence of substantial Na(+) counterions as a result of unique atomic arrangement in its structure. On the other hand, upon fast pyrolysis, followed by acid leaching, both complexes are converted into two SiO(2) composites bearing BET surface areas of 163.3 and 254.7 m(2) g(−1) for the pyrolyzed intrinsic and B-assisted Si complexes, respectively. The transesterification methodology merely involving alcoholysis but without any hydrolysis side reaction is designed to have generalized applicability for use in synthesizing new layered metal-organic compounds with tailored PBUs and corresponding metal oxide particles with hierarchical porosity.